Early versus delayed amniotomy with immediate oxytocin after Foley catheter cervical ripening in multiparous women with labor induction: A randomized controlled trial. Issue 2 (8th August 2022) - Jamaluddin, Arifah; Azhary, Jerilee Mariam Khong; Hong, Jesrine Gek Shan; Hamdan, Mukhri; Tan, Peng Chiong
Abstract: Objective: To evaluate immediate oxytocin and early amniotomy compared with delayed amniotomy after Foley catheter cervical ripening in multiparous women on intervention‐to‐delivery interval. Methods: This randomized trial was conducted in Malaysia in 232 term multiparous women with balloon catheter–ripened cervixes (dilatation ≥3 cm), singleton fetus, cephalic presentation with intact membranes, and reassuring fetal heart rate tracing. They were randomized to immediate titrated intravenous oxytocin infusion and early amniotomy (116) or delayed amniotomy after 4 h of oxytocin (116). Primary outcome was intervention (oxytocin initiation)‐to‐delivery interval. Results: Oxytocin‐to‐delivery intervals were a median of 4.99 h (interquartile range [IQR], 3.21–7.82 h) versus 6.23 h (IQR, 4.50–8.45 h) ( P < 0.001) for the early versus delayed amniotomy arms, respectively. Delivery rate at 4 h and 6 h after oxytocin infusion were 40 of 116 (35%) versus 22 of 116 (19%) (relative risk [RR], 1.82 [95% confidence interval (CI), 1.16–2.86], P = 0.011) and 77 of 116 (66%) versus 54 of 116 (47%) (RR, 1.43 [95% CI, 1.13–1.80], P = 0.003) for the early versus delayed amniotomy arms, respectively. Maternal satisfaction on birth process were 7 (IQR, 6–8) versus 7 (IQR, 7–8) ( P = 0.006), uterine hyperstimulation rates were 10 of 116 (9%) versus 14 of 116 (12%) (RR, 0.71 [95% CI, 0.33–1.54]) ( P = 0.519), and Cesarean delivery rates were 17 of 116 (15%) versus 19 of 116 (16%) (RR, 0.90 [95% CI, 0.49–1.63], P = 0.856) for the early versus delayed amniotomy arms, respectively. Conclusion: In multiparas at term following cervical ripening by Foley catheter, immediate oxytocin and early amniotomy compared with a scheduled 4‐h delay to amniotomy shortens the interval to birth and decreases uterine hyperactivity in labor but lowers maternal satisfaction. The cesarean delivery rate is not significantly reduced. Clinical Trial Registration: This study was registered with the International Standard Randomised Controlled Trial Number (ISRCTN) on September 29, 2020, with trial identification number: ISRCTN87066007 (https://doi.org/10.1186/ISRCTN87066007 ). The first participant was recruited on September 29, 2020, after ISRCTN registry confirmation was received. Synopsis: Immediate oxytocin and early amniotomy compared with delayed amniotomy after cervical ripening with Foley catheter in multiparous women hasten delivery.